2006
DOI: 10.1111/j.1398-9995.2006.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Human airway and peripheral blood eosinophils enhance Th1 and Th2 cytokine secretion

Abstract: Our data demonstrate that SEB-induced generation of Th1 and Th2 cytokines is increased in the presence of human blood and airway eosinophils. Thus, eosinophils can have an immunoregulatory function in pathogen-associated allergic diseases such as atopic dermatitis, chronic sinusitis, and asthma exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
5
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 35 publications
4
57
5
1
Order By: Relevance
“…We show that abatacept treatment significantly reduced the levels of these cytokines that are indicators of systemic inflammation, which regulates T cell responses and the proinflammatory response of eosinophils (35,36). Pathology induced by SEB is dependent upon T cell and eosinophil activation, and subsequently will lead to a systemic inflammatory response (37). We also observed that SEBdependent IL-2 expression in human and murine cell cultures was prevented by abatacept.…”
Section: Discussionsupporting
confidence: 52%
“…We show that abatacept treatment significantly reduced the levels of these cytokines that are indicators of systemic inflammation, which regulates T cell responses and the proinflammatory response of eosinophils (35,36). Pathology induced by SEB is dependent upon T cell and eosinophil activation, and subsequently will lead to a systemic inflammatory response (37). We also observed that SEBdependent IL-2 expression in human and murine cell cultures was prevented by abatacept.…”
Section: Discussionsupporting
confidence: 52%
“…The observed low concentrations of IL-4, IL-5 and IL-13 as well as the higher expression of IFN-γ in our elderly patients with AD and low total IgE were comparable to nonatopic or intrinsic AD patients [25]. Our data suggest that patients with AD and low total IgE are not sensitized to typical protein allergens that induce Th2 responses, instead, they are sensitized to staphylococcal superantigens that induce Th1 responses.…”
Section: Discussionmentioning
confidence: 77%
“…Besides the already established immediate hypersensitivity upon participation of IgE antibodies, mast cells/basophils, eosinophils and Th 2 lymphocytes, other hypersensitivity mechanisms can also be involved in this condition [1,2,3,4,5,6,7,8,9,10,11]. However, our knowledge of the role of the other mechanisms in this disorder is still relatively limited [1,2,3,6,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%